Multiscale correlations between joint and tissue-specific biomechanics and anatomy in postmortem ovine stifles - Aritra Chatterjee; Zachary Robert Davis; Timothy Lescun; Deva D. Chan (Scientific Reports)
Abstract Joint stability depends on various properties that include the bone anatomy, joint capsule geometry and stiffness, and soft tissues within. The multiscale biomechanical relationships between the whole joint and individual tissues are useful in estimating the physiological condition of the knee. To better understand these relationships, we evaluated multiple structural and mechanical parameters in healthy ovine stifles, specifically joint laxity, joint morphology, individual tissue T 2 * relaxation and mechanical properties of ligaments (ACL, PCL, MCL, LCL), patellar tendon, menisci, and cartilage. By combining mechanical testing at two length scales and magnetic resonance imaging (MRI) scans, we quantify the strength of correlation coefficients between measured metrics, among joint size, whole joint and individual tissue properties. We observe positive correlations between joint laxity forces and the inter-epicondylar distance. Further, the viscoelastic properties of the tendons and ligaments correlate positively with joint laxity forces; however, no such correlations were observed for the cartilage and menisci. We also found weak inverse correlation between tissue viscoelasticity and T 2 * for MCL; and positive correlations for cartilage and menisci, LCL and PCL respectively. These results provide useful insights into the role of individual tissues that are crucial in measuring whole joint responses as key indicators of knee health.